Features of the application of special confiscation in criminal proceedings for criminal offenses against the environment - Dudorov, O. O. (Аналітично-порівняльне правознавство, 2025)
Based on a study of recent case law and taking into account the achievements of criminal law science, this article reveals peculiarities of applying special confiscation as a criminal law measure distinct from punishment in criminal proceedings for offenses against the environment. The article critically assesses judicial practice, within which: 1) special confiscation is applied only on the basis of the provisions of criminal procedural law on material evidence, without reference to Articles 96-1 and 96-2 of the Criminal Code of Ukraine (CC), which establish the substantive legal grounds and conditions for the application of this criminal law measure; 2) preference is given to paragraph 1 of part 1 of Article 96-2 of the CC, rather than paragraph 3 of this criminal law provision; 3) legislative provisions on special confiscation are effectively ignored by the courts, despite the existence of grounds and conditions for the application of this coercive measure in specific criminal proceedings (in particular, this applies to cases of non-application of special confiscation in relation to means other than instruments used to commit criminal offenses against the environment involving the appropriation of natural resources). It has been proven that, since special confiscation can be both a sanction for committing an offense and a kind of «side effect» (for third parties) of an act committed by another person, the concept of confiscation of property enshrined in the current civil legislation needs to be clarified in a way that would take the relevant constitutional norm into account. Considerations are expressed regarding the harmonization of the provisions of criminal and criminal procedural law devoted to special confiscation. The issue of optimizing the range of criminal offenses against the environment, the commission of which makes it possible to apply special confiscation, and the purpose of applying this criminal law measure are considered. The general approaches of the Cassation Criminal Court of the Supreme Court regarding the specifics of the content of Article 1 of Protocol No. 1 to the Convention for the Protection of Human Rights and Fundamental Freedoms and the consideration of the practice of interpreting this convention provision are supported. At the same time, it is noted that: 1) there is inconsistency in the practice of the Supreme Court, which, in similar factual circumstances, in some cases finds a violation of the convention provision on the proportionality of interference with a person’s right to peaceful enjoyment of property, and in other cases does not; 2) the absence, in the Supreme Court’s decisions on environmental offences, of convincing arguments in favour of the provision on violation of the requirement of proportionality upheld by the European Court of Human Rights.